Between pedagogy and practice: developing and delivering international justice coursework in North America - Wheeldon, Johannes (Crime, law and social change, 2009)
While the need for new and innovative international coursework in North America has been recognized, developments in North American Universities have been few. Building on Mathias Reimann’s (Penn State International Law Review 22:397-415 [23]) useful justification for a new basic course in international law, this paper provides a discussion of a new approach to international justice coursework. Based on the nascent ICC and the jurisprudential developments of past international tribunals, a discrete international legal order has emerged. This may provide an opportunity for a broader examination of international criminal justice drawn from disciplines such as history, sociology, psychology, and criminology. By offering practical classroom techniques to assist in the delivery of international justice coursework, this paper attempts to provoke debate and discussion about how international coursework ought to be designed and delivered to a wider audience of undergraduate students.